Post-ovulatory ageing and egg quality: A proteomic analysis of rainbow trout coelomic fluid - Bobe Julien; Bonnet Emilie; Pineau Charles; Guitton Nathalie; Rime Hélène; Jalabert Bernard (BMC, 2004)
Abstract Background In fish, oocyte post-ovulatory ageing is associated with egg quality decrease. During this period, eggs are held in the body cavity where they bath in a semi-viscous liquid known as coelomic fluid (CF). CF components are suspected to play a role in maintaining oocyte fertility and developmental competence (egg quality). However, CF proteic composition remains poorly studied. Thus rainbow trout CF proteome was studied during the egg quality decrease associated with oocyte post-ovulatory ageing. Methods High resolution two-dimensional gel electrophoresis was used to analyze the proteome of rainbow trout (Oncorhynchus mykiss) CF in relationship with the egg quality decrease associated with oocyte post-ovulatory ageing. A first experiment was performed using CF pools originating from 17 females sampled at ovulation as well as 7, 14 and 21 days later. These observations were verified using a second set of CF pools originating from 22 females sampled 5 and 16 days following ovulation. Results Approximately 200 protein spots of 10-105 kDa molecular mass and 3-10 pI were detected in CF samples. Several protein spots, while undetected at the time of ovulation, exhibited a progressive and strong accumulation in CF during post-ovulatory ageing. After silver-staining and Matrix-Assisted Laser Desorption Time Of Flight (MALDI-TOF) mass spectrometer analysis, some of these protein spots were identified as lipovitellin II fragments. Conclusions These observations suggest that egg protein fragments accumulate in the CF during the post-ovulatory period and could therefore be used to detect egg quality defects associated with oocyte post-ovulatory ageing.